Self-Concept, Attitudes Toward Career Counseling, and Work Readiness of Malaysian Vocational Students - Poh Li Lau; Tina Anctil; Guan, Teik Ee; Jas Laile Suzana Jaafar,; Teoh Gaik Kin (2020)
The authors examined the relationship between self‐concept, attitudes toward career counseling, and work readiness among 574 Malaysian vocational students. Attitudes toward career counseling have been studied in Western cultures; however, little is known about how career counseling is perceived in Eastern cultures. Attitudes toward career counseling were examined as a potential mediator of the relationship between self‐concept and work readiness. The authors applied structural equation modeling to explain these relationships. Value of career counseling was found to significantly mediate the link between self‐concept and work readiness. Results supported a direct relationship between positive self‐concept and work readiness skills. This may be due, in part, to a heightened value of career counseling among vocational students that increases career awareness and thus enhances work readiness. Future research could include samples with more female participants and additional constructs, such as self‐efficacy and career adaptability.